A Fossil History of Southern African Land Mammals - Margaret Avery, D. (Physical Sciences, 2019)
A comprehensive reference on the taxonomy and distribution in time and space of all currently recognized southern African fossil mammals, covering the Eocene to the Holocene, with individual maps marking locations. This title is also available as Open Access on Cambridge Core.